2013
DOI: 10.1074/jbc.m112.425249
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Regulation of Serine/Threonine Protein Kinase (AKT) Genes by Glioma-associated Oncogene Homolog 1

Abstract: Background: Little is known regarding the transcriptional regulation of AKT. Results: GLI1 contributes to the survival of DLBC cells by promoting transcription of AKT genes. Conclusion: AKT1 is a novel direct downstream target of the Hedgehog transcriptional factor GLI1. Significance: Identifying target genes of GLI1 provides insights into the contribution of Hedgehog signaling in the pathobiology of malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Other groups have shown that the AKT1 promoter possesses two GLI1 binding sites (BS1 and BS2) and proved the expression of AKT1 was regulated at the transcriptional level by GLI131. Our results suggested that for AML patients with both GLI1 and AKT activation, the GLI1 inhibitor alone is sufficient, which will significantly decrease the unnecessary side effects of the combination therapy using Hh and PI3K inhibitors.…”
Section: Discussionsupporting
confidence: 59%
“…Other groups have shown that the AKT1 promoter possesses two GLI1 binding sites (BS1 and BS2) and proved the expression of AKT1 was regulated at the transcriptional level by GLI131. Our results suggested that for AML patients with both GLI1 and AKT activation, the GLI1 inhibitor alone is sufficient, which will significantly decrease the unnecessary side effects of the combination therapy using Hh and PI3K inhibitors.…”
Section: Discussionsupporting
confidence: 59%
“…GLI1, a zinc finger transcriptional factor of the Hedgehog signaling, increases the transcription of of AKT1, AKT2 , and AKT3 genes [32]. AKT1 promoter possesses two GLI1 binding sites (BS1 and BS2) located upstream of the transcriptional start site of AKT1 gene.…”
Section: Upstream Regulatory Pathways Of Aktmentioning
confidence: 99%
“…The homology of each GLI1 binding site to the consensus sequence was 67% for BS1 and 78% for BS2. AKT2 and AKT3 promoters also contain three and two GLI1 binding sites, respectively [32]. …”
Section: Upstream Regulatory Pathways Of Aktmentioning
confidence: 99%
“…Moreover, regulation of cMYC [71,72] and possibly of AKT [73] by GLI1, may establish positive feed-forward loops. Together, this insures that GLI1 activity will increase as tumor suppressors are lost and oncogenes gained.…”
Section: Regulation Of the Gli Code By Non-hh Signals And By The Oncomentioning
confidence: 99%